Contributions to a history of New Zealand lichenology 5*. James Murray (1923–1961) - Galloway, David John (Phytotaxa, 2015)
James Murray (1923–1961), an organic chemist by profession, was also New Zealand’s first modern lichenologist. Having a wide knowledge of New Zealand plants, and a very competent grasp of post-war natural product chemistry, he was well qualified to take up lichens at a period when chemosystematics was just becoming important in the group. His early published work was to influence the emerging field of lichen bioactive compounds, and 50 years later, generic concepts in the Lobariaceae. Murray’s joint careers in organic chemistry and lichenology were tragically cut short by his early accidental death; his legacy being a handful of papers and an extensive lichen herbarium (now at OTA). However, James Murray’s example and influence have resonated much more widely than these concrete accomplishments. To enable his contributions to be properly appreciated, the present biographical memoir outlines his life, work and legacy to modern lichenology. The genus Yarrumia D.J.Galloway is described in Murray’s honour and two new combinations are made: Y. colensoi (C.Bab.) D.J.Galloway and Y. coronata (Müll.Arg.) D.J.Galloway.